Analysis of the local resource-based dairy cattle development in Central Java - Mukson, M.; Setiyawan, H.; Handayani, M.; Setiadi, A. (Diponegoro University, 2017)
The objectives of this research wereto analyze the local resource-based development of dairy cattle in orderto improve the production and quality of milk in Central Java. The research wascarried out by survey method. The research locations (Boyolali and Semarang) were chosen using purposive sampling method.In each regency was determined 2 sub district locations in which having the largest dairy cow population and 3 Dairy Cattle Farmer Associations (DCFA) in every sub district.Dairy farmers were sampled randomly, 10 farmers in every DCFA. Therefore, there were 120 dairy cattle farmers for sample. Data wereanalyzed using descriptive methods, location quotient (LQ) analysis and multiple linear regression statistical model. The dependent variables were yield and quality of milk (Y1,2) and the independent variables were human resources (x1), environmental resources (x2), capital resources (x3), entrepreneurship resources (x4), technology resources (x5), institution resources (x6) and infrastructure resources (x7). The LQ analysis showed that dairy cattle population, availability of forage and agricultural waste, and absorption of labour were very potential (LQ>1). Local resources significantly affected (P<0.01) the production and quality of dairy cattle milk. These results suggest that the development of dairy cattle business needs to consider the potential of local resources in order to improve the production and quality of milk.